Penggunaan Antiseptik untuk Mencegah Pin Site Infection pada Pasien Terpasang Eksternal Fiksator - Meitri, Wella; Masfuri, Masfuri (Journal of Telenursing (JOTING), 2023)
This study aims to review antiseptics that can be used in pin-site care to prevent pin-site infection in patients with external fixators. The research method is a systematic review, which begins with the article selection process through PRISMA, followed by an article review process to determine which articles can be reviewed. The results of a systematic review of six articles showed the benefits of using antiseptics for pin site care in preventing pin site infections. Combining chlorhexidine with other antiseptics such as alcohol and 1% silver sulphadiazine, single use of chlorhexidine, povidone iodine, emollient, and microbicidal liquid polymer has proven effective in preventing pin site infection. Chlorhexidine is considered to be used in low concentrations to minimize the risk of skin irritation. Povidone iodine has the advantage of being an antiseptic that can be easily found in hospitals and is cheap. In conclusion, antiseptics can be used to prevent pin site infections. Still, emollient skincare, a combination of 5% chlorhexidine - 1% silver sulphadiazine, and microbicidal liquid polymer still require further research due to the lack of literature and the use of ingredients that are not yet familiar. Keywords: Antiseptic, Patient Installed External Fixator, Pin Site Infection